Debt To Equity Ratio Dan Total Assets Turnover Sebagai Determinan Return On Equity Pada Perusahaan Property Dan Real Estate - Muhammad Basri (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2020)
This study aims to examine the partial or simultaneous effect of Debt to Equity Ratio (DER) and Total Assets Turnover (TATO) on Return On Equity (ROE) as the dependent variable on Property and Real Estate Companies on the Indonesia Stock Exchange. Associative research approach. Sources of data used in this study is secondary data in the form of company financial statements for the last 5 years. The data analysis technique in this study used multiple linear regression analysis techniques. The results of this study indicate that the Debt to Equity Ratio (DER) partially has an effect on Return On Equity (ROE) while Total Assets Turnover (TATO) partially has a significant effect on Return On Equity (ROE), and simultaneously, Debt to Equity Ratio (DER), and Total Assets Turnover (TATO) have a significant effect on Return On Equity (ROE) in Property and Real Estate Companies listed on the Indonesia Stock Exchange.